Influence Investment, Financing, and MSMEs Against Growth Medan City Community Economy 2017-2022 - Gaja, Enita Indramayani; Batubara, Maryam; Marliyah, Marliyah (Quantitative Economics and Management Studies, 2024)
This study aims to analyze the influence of investment, financing, and MSMEs on the economic growth of Medan City from 2017 to 2022. It is a quantitative research study conducted through library research and reference studies. Data collection methods include questionnaires and documentation studies. The data analysis involves validity and reliability tests, classical assumption tests, t-tests (partial), F-tests (simultaneous), regression analysis, and coefficient determination. The results indicate that investment, financing, and MSMEs play significant roles in the economic growth of Medan City. Investment contributes 14.1% to economic development by enhancing infrastructure and technology, which supports the industrial sector and creates job opportunities. Financing, with a 99.1% contribution, facilitates business access to capital, improves efficiency, production capacity, innovation, and supports economic diversification. Although MSMEs contribute only 1.9%, they are crucial for the local economy by providing employment and reducing poverty. Supportive pro-MSME policies are essential for their growth. Overall, these three variables contribute 97.5% to the economic growth of Medan City's community between 2017 and 2022, underscoring their key roles in driving local economic development.